THE EFFECT OF FINANCIAL KNOWLEDGE AND PERSONAL NET INCOME ON THE FINANCIAL BEHAVIOR OF MALIKUSSALEH UNIVERSITY EMPLOYEES WITH LOCUS OF CONTROL AS MODERATING VARIABLES - Aryani, Risa; Khaddafi, Muammar; Naz'aina, Naz'aina (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
The Influence of Financial Knowledge and Personal Net Income on Financial Bihaviour of Universitas Malikussaleh Employees with Locus Of Control as Moderation Variable. The purpose of this study was to determine how the model of financial behaviour of civil servants and lecturers in the Malikussaleh University environment and what factors are the most powerful in influencing the financial behaviour of employees in the Malikussaleh University campus environment. The research sample taken from the population in this study were 261 Civil Servants Group II to Group IV in Universitas Malikussaleh. The method used to support this research is quantitative method and in this study using multiple linear regression models. The processing and interpretation of research data using statistical software SmartPLS. The results of data analysis in this study indicate that financial knowledge has a positive and insignificant effect on the financial behaviour of Universitas Malikussaleh employees. Personal net income has a positive and significant effect on the financial behaviour of Universitas Malikussaleh employees. Locus of control does not moderate the effect of financial knowledge on financial behaviour of Universitas Malikussaleh employees. Locus of control does not moderate the effect of personal net income on the financial behaviour of Universitas Malikussaleh employees.